The Participation of Member-Farmers in Increasing The Role of Gapoktan on The Program of Potato’s Farmers Community Empowerment in Batu City - Sugiyanto, Sugiyanto (International Journal of Social and Local Economic Governance, 2017)
Potato (Solanum Tuberosum L.) is one of the main staple foods for the people of East Java besides rice, wheat and corn. In addition, potatoes are also a high quality commodity of vegetable that have high-value and until now potatoes have the potential value to be developed as a source of carbohydrate in supporting food diversification program, increasing farmers' income, non-oil export commodities and raw materials of processed industries. After harvesting potatoes it is common happen the respiration and the transpiration process on the potato tubers, this is due to the high water content of potato, so that at one time the quality will experience a decline due to metabolic processes and cannot be stored a long time in fresh form. However, the development of potato commodities is still faced with several problems, some examples are on the low participation of farmers in the role of Gapoktan development and the empowerment of farmers in terms of mastery in potatoes products processing that require the varieties and also the special cultivation in order to produce potato tubers that available with special requirements.